Immunohistochemical Evaluation of Fibronectin and Tenascin Following Direct Pulp Capping with Mineral Trioxide Aggregate, Platelet-Rich Plasma and Propolis in Dogs’ Teeth - Moradi, Saeed; Saghravanian, Nasrollah; Moushekhian, Siavash; Fatemi, Samar; Forghani, Maryam (Iranian Endodontic Journal, 2015)
Introduction: The aim of the present study was to evaluate the expression of fibronectin (FN) and tenascin (TN) after direct pulp capping (DPC) in dogs’ teeth with either mineral trioxide aggregate (MTA), Propolis or Platelet-rich plasma (PRP), by means of immunohistochemistry. Methods and Materials: A total of 48 sound molars and premolars with mature apices from four dogs, were included. The teeth were randomly divided into 4 groups according to the material used for DPC: PRP, Propolis, MTA, and glass-ionomer (as the negative control group). Each group was divided into two 7-day and 30-day subgroups. The teeth were restored at the same session. The animals were sacrificed at the mentioned time intervals and the expression of FN and TN in each test group and between each time intervals was assessed with Wilcoxon and Mann-Whitney U tests, respectively. The Kruskal-Wallis test was used to compare FN and TN staining among the test groups. The significance level was set at 0.05. Results: The amount of FN in the MTA group in the 30-day interval was significantly higher than the 7-day interval; however, there were no significant differences among the other groups. The amount of TN in the MTA and Propolis groups in the 30-day interval was significantly higher than that in the 7-day interval; no recognizable difference was observed in the other groups. Moreover, the difference in expression of FN and TN in the 7-day interval was not significant in the experimental groups. Nevertheless, the difference was significant in the 30-day interval, with the highest and lowest expressions belonging to the MTA and glass-ionomer groups, respectively. Conclusion: Based on the results of the present animal study, MTA is still a better choice for direct pulp capping. Keywords: Fibronectin; Immunohistochemistry; Propolis; Pulp Capping; Tenascin